Buddhists, brahmins, and belief: epistemology in South Asian philosophy of religion - Arnold, Daniel Anderson (Columbia University Press, 2005)
In Buddhists, Brahmins, and Belief, Dan Arnold examines how the Brahmanical tradition of Purva Mimamsa and the writings of the seventh-century Buddhist Madhyamika philosopher Candrakirti challenged dominant Indian Buddhist views of epistemology. Arnold retrieves these two very different but equally important voices of philosophical dissent, showing them to have developed highly sophisticated and cogent critiques of influential Buddhist epistemologists such as Dignaga and Dharmakirti. His analysis -- developed in conversation with modern Western philosophers like William Alston and J. L. Austi